Co-management of Reservoir Fisheries for Sustainable Livelihoods: Insights for Fishery Managers and Extension Professionals from Field Studies in India - L.K. Tyagi , A.S. Bisht; Amar Pal (Indian Journal of Extension Education, 2015)
Reservoirs hold tremendous potential for inland fisheries development and offer ample scope for fish yield optimization through adoption of appropriate management measures. H owever, there are several socio-economic issues involved in their management as communities displaced due to creation of these reservoirs depend upon them for earning livelihoods.Reservoirs hold tremendous potential for inland fisheries development and offer ample scope for fish yield optimization through adoption of appropriate management measures. Governance and management pattern of these reservoirs varies in different states of India and faces several challenges including the twin pressures, to increase the production and productivity, and ensure sustainable livelihoods for communities dependent upon these resources. The present paper while discussing these issues elaborates upon the co-management approach to address them. Citing synthesized overall summary of the major findings of the field studies done in Northern, Central and Eastern India, the paper elaborates upon the performance of fishing cooperative societies in co-management and conservation of reservoir fishery resources and roles played by various stakeholders and their linkages in this endeavor. The paper is based on review of literature, secondary data from various records, and primary data gathered and detail interactions had with several stakeholders during field studies in four states of India namely, Madhya Pradesh, Himachal Pradesh, Uttar Pradesh and Orissa covering 57 fishing cooperative societies and 875 respondents. The findings indicated that local communities and their organizations (fishing cooperative societies/federations) can play important role in collective management of reservoir fisheries under the situations where some of the facilitating conditions for promoting collective action are present. The paper concludes that governance and management of reservoir fisheries need to be viewed in light of the recent developments and empirical evidences made available by the social scientists in natural resource management. There is tremendous scope for innovation in their governance. Lessons drawn from successes achieved in various forms of co-management fisheries resources, such as reported here and elsewhere across the globe, need to be incorporated in devising policies and programmes for management of reservoir fisheries. The field of fisheries management and conservation presents enormous possibilities for the extension professionals to broaden their canvas and contribute policy oriented studies to help the fisheries managers and policy makers in further improving the sector.